2013
DOI: 10.1016/j.rbmo.2013.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian hormone versus antral follicle count for defining the starting dose of FSH

Abstract: This pilot study compared the efficacy and safety of two simple dosing algorithms, one based on anti-Müllerian Hormone (AMH) and the other on the antral follicle count (AFC), to determine the starting dose of recombinant FSH (rFSH) for ovarian stimulation in 348 women. Patients were randomized to a predefined AMH- or AFC-based algorithm. The proportion of cycles with the desired response was similar when rFSH dose was determined using AMH or AFC (35.2% versus 28.4%). There was a significant difference between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 41 publications
7
32
0
1
Order By: Relevance
“…Yet, the GnRH‐antagonist protocol has been adopted increasingly in recent years for its simplicity and lower risk of ovarian hyperstimulation syndrome associated with its use. Therefore, the findings from the present study, which essentially concur with those of Lan et al ,. reinforce our knowledge on this issue as applied to IVF cycles following the GnRH‐antagonist protocol.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Yet, the GnRH‐antagonist protocol has been adopted increasingly in recent years for its simplicity and lower risk of ovarian hyperstimulation syndrome associated with its use. Therefore, the findings from the present study, which essentially concur with those of Lan et al ,. reinforce our knowledge on this issue as applied to IVF cycles following the GnRH‐antagonist protocol.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the respectable sample size included, these meta‐analyses were based on different studies with possible heterogeneity and biases incurred. To our knowledge, there has been only one randomized trial comparing the AFC‐based and AMH‐based gonadotropin‐dosing algorithms, which showed no difference in the proportion of women having the desired number of oocytes retrieved in either group. In that study, it was not known if the subjects and clinicians were blinded, and women were treated exclusively following the long GnRH‐agonist protocol.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several different algorithms, in which AMH levels play the main role, have been proposed. These studies have mainly focused on the response to the initial dose of FSH during the assisted reproduction cycle [20][21][22], and successful reduction of unwanted responses (cycle cancellation or OHSS) has been reported [18,22,23].…”
Section: Algorithm For the Selection Of Ovarian Stimulation Protocolsmentioning
confidence: 99%
“…Recent research has targeted developing specific ovarian stimulation protocols individualized by AMH results [16 ▪▪ ,17 ▪ ]. Other recent studies focus on refining information such as demonstrating that an AMH value from a single point in time will remain predictive for approximately 12 months [18], how certain stimulation protocols affect different patient phenotypes such as PCOS vs. low responders [19 ▪▪ ,20], and prospectively demonstrating that application of AMH testing can improve expectation management and possibly treatment costs [21].…”
Section: Oocyte Quantity and Quality Fertility Treatment And Naturamentioning
confidence: 99%